2017
DOI: 10.1016/j.ebiom.2017.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Potent and Selective BACE-1 Peptide Inhibitors Lower Brain Aβ Levels Mediated by Brain Shuttle Transport

Abstract: Therapeutic approaches to fight Alzheimer's disease include anti-Amyloidβ (Aβ) antibodies and secretase inhibitors. However, the blood-brain barrier (BBB) limits the brain exposure of biologics and the chemical space for small molecules to be BBB permeable. The Brain Shuttle (BS) technology is capable of shuttling large molecules into the brain. This allows for new types of therapeutic modalities engineered for optimal efficacy on the molecular target in the brain independent of brain penetrating properties. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…Sequence alignment analysis showed that the amino acid sequences of human BACE1 and BACE2 gene coding regions are 45% identical and 75% homologous [22]. Numerus crystal structures of BACE1 have been resolved with and without inhibitor in its active site [23][24][25][26][27][28][29][30][31][32]. BACE1 contains an N-terminal protease domain, a connecting strand, a transmembrane region, and a cytosolic domain [23].…”
Section: Function and Structure Of β-Secretasementioning
confidence: 99%
“…Sequence alignment analysis showed that the amino acid sequences of human BACE1 and BACE2 gene coding regions are 45% identical and 75% homologous [22]. Numerus crystal structures of BACE1 have been resolved with and without inhibitor in its active site [23][24][25][26][27][28][29][30][31][32]. BACE1 contains an N-terminal protease domain, a connecting strand, a transmembrane region, and a cytosolic domain [23].…”
Section: Function and Structure Of β-Secretasementioning
confidence: 99%
“…B63 antibody binds to full length APP (FL APP) and C-terminal fragments (CTF, longer exposure). 82E1 antibody speci cally detects human Aβ (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16), and hence the human B-CTF, independently con rming that the rat App gene was successfully humanized. β-ACTIN was used as a loading control.…”
Section: Availability Of Data and Materialsmentioning
confidence: 99%
“…We have modelled the interaction of humanized β-CTF with BACE1, using as a template the published crystal structure of BACE1 in combination with an active site peptide inhibitor (PDB ID 5MCQ) (16). The sequence of the humanized β-CTF was aligned to the peptide in 5MCQ, aligning residue E11 from the humanized β-CTF sequence to the STA query (Threonine) of the crystallized peptide (Fig1).…”
Section: Computational Model Of the Humanized β-Ctf Bound To Bace1mentioning
confidence: 99%
See 2 more Smart Citations